Caring for children with neurofibromatosis type 1. Issue 4 (April 2019) - Sampson, Janice; Thompson, Heather L.; Parilo, Denise M. Wall
Abstract : Abstract: This article discusses the variable physical manifestations of neurofibromatosis type 1 among children in terms of presentation, disease severity, and prognosis, and addresses appropriate nursing interventions and patient teaching. Abstract : In children, the manifestations of neurofibromatosis type 1 vary widely in terms of presentation, disease severity, and prognosis. Here, the authors address appropriate patient assessment, nursing interventions, and education for children and adolescents with this surprisingly common genetic disorder.